Modeling and simulation of a novel 4.5 kWe multi-stack solid-oxide fuel cell prototype assembly for combined heat and power. (15th May 2017) - Anyenya, Gladys A.; Sullivan, Neal P.; Braun, Robert J.
Highlights: A novel CHP application of SOFC technology in unconventional oil and gas processing. Thermo-electrochemical performance model of a multi-stack solid-oxide fuel cell (SOFC) assembly is described. Parametric study explores a wider range of operating conditions than can be experimentally tested. Geothermic Fuel Cell operational characteristics are reviewed. Abstract: The United States Geological Survey estimates that over four trillion barrels of crude oil are currently trapped within U.S. oil shale reserves. However, no cost-effective, environmentally sustainable method for oil production from oil shale currently exists. Given the continuing demand for low-cost fossil-fuel production, alternative methods for shale-oil extraction are needed. Geothermic Fuel Cells™ (GFC) harness the heat generated by high-temperature solid oxide fuel cells during electricity generation to process oil shale into "sweet" crude oil. In this paper, a thermo-electrochemical model is exercised to simulate the performance of a 4.5 kW e (gross) Geothermic Fuel Cell module for in situ oil-shale processing. The GFC analyzed in this work is a prototype which contains three 1.5 kW e solid oxide fuel cell (SOFC) stack-and-combustor assemblies packaged within a 0.3 m diameter, 1.8 m tall, stainless-steel housing. The high-temperature process heat produced by the SOFCs during electricity generation is used to retort oil shale within underground geological formations into high-value shale oil and natural gas. A steady-state system model is developed in Aspen Plus™ using user-defined subroutines to predict the stack electrochemical performance and the heat-rejection from the module. The model is validated against empirical data from independent single-stack performance testing and full GFC-module experiments. Following model validation, further simulations are performed for different values of current, fuel and air utilization to study their influence on system electrical and heating performance. The model is used to explore a wider range of operating conditions than can be experimentally tested, and provides insight into the competing physical processes at play during Geothermic Fuel Cell operation. Results show that the operating conditions can be tuned to generate desired heat-flux conditions as needed across applications.